Digitalization in mathematics education: how distance and online learning shape pre-service teachers’ career perceptions - Dinçer, Bahar (Frontiers in Education, 2025)
This study examines the perceptions of pre-service mathematics teachers with prior experience in distance education and engagement with digital tools regarding online and distance education, their professional perspectives, and their tendencies toward digital content creation. The findings indicate that while distance education enhances pedagogical flexibility, it also positions digital content creation as an essential professional skill. Participants recognize the effectiveness of digital tools in conveying mathematical concepts’ abstract and visual aspects but acknowledge gaps in their competencies. The most striking finding reveals that shifting employment conditions push pre-service teachers to explore alternative career paths through digital platforms, with online teaching increasingly seen as a sustainable option rather than a temporary solution. This transformation fosters awareness of the necessity to develop digital pedagogical skills while urging teacher education programs to integrate digitalization strategies. Providing evidence of how digitalization reshapes teaching, this study underscores that digital competencies are no longer optional but a necessity.